Respostas

2013-08-20T14:40:20-03:00
Delta:b^{2} -4.a.c
delta:6^{2} -4.1.8
delta:36-32
delta:4
rais de delta : raiz de 4 : +_ 2
x=-b+_raiz de delta/2.a
x=-6+_2/2.1
x=-6+2/2=-4/2=-2
x=-6-2/2=-8/2=-4
beijoosss espero que goste
6 4 6
2013-08-20T14:40:48-03:00
X²+ 6x +8 =0
Pelo método de completar quadrados seria assim:
x²+3*x*2+..... = ..... -8
x²+6x +9= 9-8
(x + 3)²= 1
x+ 3= 1
x= -3+1
x= -2
Por bhaskara:
a: 1  b:6 c: 8
Delta= 6² -4*8*1
Delta= 36 -32
Delta= 4
Raiz de Delta= 2
(-6 +/- 2)/2=x
x¹= -4
x²=-2
4 3 4